Intensi Berhenti Merokok pada Mahasiswa Perokok Sosial Ditinjau dari Theory of Planned Behavior - Widodo, Rizki Alivia Putri; Leonardi, Tino (Buletin Riset Psikologi dan Kesehatan Mental, 2025)
Among students, social smoking is a behavior that is primarily carried out in social situations in order to be more accepted by the social environment. This study aims to examine the intention to quit smoking among students who are social smokers based on the Theory of Planned Behavior (TPB). This cross-sectional study involved 102 students in Indonesia aged 18–25 years. The TPB scale (α = .915) was used to measure predictors of intention, and the Smoking Cessation Intention scale (α = .883) was used to measure intention to quit smoking. The data in this study were analyzed using multiple linear regression. The results of the data analysis showed that attitudes toward smoking cessation behavior (B = .263, SE =.109; p = .017) and subjective norms (B = .712, SE = .172, p <.001) significantly explained in smoking cessation intention (F(3,98) = 27.8, p < .001, R² = .460).